2003
DOI: 10.1111/j.1432-2277.2003.tb00235.x
|View full text |Cite
|
Sign up to set email alerts
|

Organ-specific response to inhibition of mitochondrial metabolism by cyclosporine in the rat

Abstract: To evaluate organ-specific metabolic changes after in vivo cyclosporine (CyA) treatment, male Wistar rats were treated with 10 mg/ kg per day CyA orally for 6 days. Blood, kidney, liver, and heart tissues were extracted and analyzed by magnetic resonance spectroscopy (MRS). CyA decreased the energy balance [adenosine triphosphate (ATP)/adenosine diphosphate (ADP)] in all organs (kidney [control]: 50%, liver: 64%, and heart: 62%, all P < 0.01) due to decreased activity of the mitochondrial Krebs cycle and oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 20 publications
0
8
2
Order By: Relevance
“…A likely explanation for this discrepancy in comparison with a previous study [37] is the difference in kidney tissue collection. ATP/ADP concentrations in tissue are extremely sensitive to hypoxia.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…A likely explanation for this discrepancy in comparison with a previous study [37] is the difference in kidney tissue collection. ATP/ADP concentrations in tissue are extremely sensitive to hypoxia.…”
Section: Discussioncontrasting
confidence: 52%
“…Earlier studies assessing cyclosporine toxicity had shown that inhibition of oxidative phosphorylation in brain mitochondria and kidneys may lead to a decrease in high-energy metabolites [9, 37]. However, our analysis of high-energy metabolites in kidney tissue 7 days after kidney transplantation indicated a significant decrease in ATP and NAD kidney tissue concentrations only in group 6 compared with untreated nontransplant controls.…”
Section: Discussioncontrasting
confidence: 49%
“…The pH was adjusted to 5.65-5.75 with NaOD and DCl. Methanol : chloroform extraction of whole blood was carried out in the same manner as described previously [31][32][33]. All extraction steps were carried out on ice.…”
Section: Analysis Of Metabolite Profiles Using 1 H-nmr Spectroscopymentioning
confidence: 99%
“…Calibration curves of key metabolites as measured by 1 H-NMR. Heparinized whole blood was enriched with the metabolites and extracted using a methanol : chloroform extraction procedure [31][32][33]. Abbreviations: GSH, glutathione; Glu, glutamate; TMAO, trimethylamine oxide.…”
Section: Figurementioning
confidence: 99%
“…tissue, cells and body fluids) in response to pathological stimuli or genetic modifications . Nuclear magnetic resonance (NMR) spectroscopy is one of the well‐suited and popular techniques in metabolomics, which permits the simultaneous detection, identification and quantification of several hundreds of metabolites in the biological matrix, and especially in urine . NMR‐based metabolomics studies of urine samples have been successfully used to identify the metabolomics fingerprints and potential biomarkers in a few renal diseases, including focal segmental glomerulosclerosis, renal transplant dysfunction and chronic renal failure; however, there are a limited number of metabolomics studies in IgAN.…”
Section: Introductionmentioning
confidence: 99%